Customer Relationship Management yang Berkelanjutan - Setyawati, Harini (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
CRM (Customer Relationship Management) is a new approach to managing the relationship between companies and business customers, aiming to maximize communication, marketing, and added value for customers. By integrating company policies, processes, and strategies, CRM enables effective interaction with customers and management of customer information. The implementation of CRM typically utilizes information technology to attract and retain profitable customers. The primary objective of CRM in business is to enhance relationships with existing customers and provide comprehensive information to increase sales through up-selling and cross-selling, ultimately aiming to boost company profits.